The role of drain placement in post-bariatric surgery bleeding and leak detection: Palestinian main center experience (2017–2021) - Fatima az-Zahra Mohammed Thawabteh; Taqwa Riad Abu Ghanieh; Osama J. Makhamreh; Khaled Alshawwa; Bayan Fathi Al-Qtishat; Ruba Maher Salameh; Omar Abu Zaydeh (BMC Surgery)
Abstract Introduction Bariatric surgery, such as sleeve gastrectomy (SG) and gastric bypass, is a common option for weight loss in patients with obesity and metabolically ill individuals. However, complications like bleeding and leaks can occur. Surgeons often use intraoperative drains to detect these issues, but their effectiveness is debated due to conflicting evidence. Our study aims to evaluate the benefits of intra-abdominal drains in detecting postoperative bleeding and leaks. Methods This is a retrospective cross-sectional study, with data from 494 patients who underwent bariatric surgery at the primary bariatric center in Palestine, between 2017 and 2021. Patient demographics, comorbidities, surgical complications, and drain usage were collected, managed, and analyzed using SPSS. Results The study included 494 patients, predominantly females (69.0%) with a median age of 39.5 years. Sleeve gastrectomy was the most common procedure (78.1%). Postoperative complications occurred in 3.0% of patients, with bleeding being the most prevalent (1.4%). Drain placement was routine (82.0%), but no significant correlation was found between drain output volume and signs of bleeding, such as heart rate and blood pressure. However, a weak inverse correlation was observed between volume for bloody drain character and hemoglobin levels on the first postoperative day. Conclusion Drains are commonly used in bariatric surgery; however, their effectiveness in detecting complications like bleeding and leaks remains uncertain. There was no association between drain output volume and signs of bleeding and leak complications, and the clinical assessment, especially the vital signs, is the most effective method in identifying postoperative issues. Clinical trial number Not applicable.